Case of -induced Brain Abscess Mimicking Brain Tumor - Yoonhyuk Jang; Jangsup Moon; Jin-Sun Jun; Tae-joon Kim; Kyung-Il Park; Soon-Tae Lee; Keun-Hwa Jung; Sang Kun Lee; Kon Chu (Osong Public Health and Research Perspectives, 2018)
Murine typhus is one of the most prevalent rickettsial infections in the world, caused by the bacterial genus Rickettsia. Though the disease manifests a relatively benign clinical course with fever, rash, and headache being the 3 classic symptoms, neurological complications may arise in patients that could become permanent. In this case study, a patient with a brain abscess caused by R typhi infection is described. Based upon the recent reemergence of arthropod-borne disease, the findings in this case are significant; R typhi can cause a brain abscess that mimics a brain tumor, which delays the diagnosis and appropriate management of the disease. Murine typhus should always be considered when performing the differential diagnosis of brain abscesses in South Korea.